Aquilaria subintergra leaves extracts as sustainable mild steel corrosion inhibitors in HCl. (October 2017) - Sin, Helen Lee Yun; Abdul Rahim, Afidah; Gan, Chee Yuen; Saad, Bahruddin; Salleh, Muhammad Idris; Umeda, Minoru
Highlights: Aquilaria subintegra leaves extracts has IE % up to 93 % for mild steel in 1 M HCl. Extracts adsorb by physisorption to protect the mild steel from corrosive medium. Reporting five compounds present in Aquilaria subintegra leaves. Among the reported compounds, adenosine exhibits good corrosion inhibition. Abstract: The leaves extracts from non and inoculated Aquilaria subintegra were tested and were shown to have high corrosion inhibition of up to 93% at 1500 ppm using methods such as the weight loss study, electrochemical impedance spectroscopy measurement and potentiodynamic polarization measurement. The electrochemical measurements showed that the leaf extract from the chemically inoculated tree was the best inhibitor, while weight loss study showed that all the extracts have similar inhibition efficiencies. The extracts were shown to adsorb on the surface of mild steel by physisorption process from the Langmuir adsorption isotherm model and the potential zero charge analysis. The leaves extracts were analyzed using the Quadrupole-Time of Flight Liquid Chromatogram/ Mass spectrometer (Q-TOF LC/MS) and five compounds were successfully identified in Aquilaria subintegra . Among the identified compounds, adenosine was found to be an excellent inhibitor with an inhibition efficiency of up to 62% at a very low concentration (1 × 10 −4 M).